The Development of English Language Speaking Skills for Students Under the Conditions of Distance Learning - Bekkulova Hojar Zayniddinovna (Genius Journals, 2021)
The article touches upon the topical issue of developing the skills of speaking a foreign language among students of 9 grade of a general education school in the context of distance learning. As a solution to the problem of developing oral speech skills in a foreign language, the author proposes to introduce authentic poetic materials into the process of teaching a foreign language in the classroom, gives the stages and methods of working with them using the example of one poem, and also proposes author's exercises developed on the basis of the use of authentic poetic texts
Keywords: Speaking Skills; Teaching A Foreign Language; Distance Learning; Techniques for Working with Poetic Text